2015
DOI: 10.15585/mmwr.mm6436a2
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination Coverage Among Pregnant Women — United States, 2014–15 Influenza Season

Abstract: Pregnant women and infants are at increased risk for influenza-related complications and hospitalization. Influenza vaccination can reduce the risk for influenza-related illness among pregnant women and their infants. Since 2004, the Advisory Committee on Immunization Practices (ACIP) and the American College of Obstetricians and Gynecologists (ACOG) have recommended influenza vaccination for all women who are or will be pregnant during the influenza season, regardless of trimester of pregnancy. To assess infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
78
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 9 publications
12
78
2
1
Order By: Relevance
“…Our findings are consistent with studies from countries where the vaccination coverage rates are higher when there is receipt of vaccine recommendation, especially when receiving both a recommendation and an offer of vaccination [1517]. Specifically, in the United States during the 2014–15 influenza season, vaccination coverage among pregnant women who received an influenza vaccination recommendation and a vaccine offer was approximately 68% compared to 34% among those who received a recommendation but not an offer, and 8.5% among those who did not receive a recommendation nor an offer [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with studies from countries where the vaccination coverage rates are higher when there is receipt of vaccine recommendation, especially when receiving both a recommendation and an offer of vaccination [1517]. Specifically, in the United States during the 2014–15 influenza season, vaccination coverage among pregnant women who received an influenza vaccination recommendation and a vaccine offer was approximately 68% compared to 34% among those who received a recommendation but not an offer, and 8.5% among those who did not receive a recommendation nor an offer [16]. …”
Section: Discussionmentioning
confidence: 99%
“…These strategies do not take into account specific patient attitudes; however, these strategies have been shown to work regardless of patient attitude [8]. Yet attitudes play a role in accepting vaccination as evidenced by a study of pregnant women which found the percentage vaccinated among women recommended and offered vaccine by their physician was 77.2% for those with a positive attitude about vaccine efficacy compared with 15.4% for those with a negative attitude; the percentages vaccinated were 79.2% for those with a positive and 26.1% for those with a negative attitude about vaccine safety [9]. An exploration of reasons for non-vaccination, by quantifying the most common reasons given for non-vaccination, could be useful to healthcare providers and immunization programs so that they are better prepared to address the concerns of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these recommendations, the concept of maternal immunization has not been widely accepted by the general public or healthcare providers. Vaccination rates in pregnant women remain suboptimal in many countries and are still much lower than those in children [71,73,74,114]. One of the key reasons is that clinical trial data on efficacy or safety during pregnancy are limited for most vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…50% in the US, 40À65% in the UK, <25% in other European countries or <2% in Hong Kong), with some exceptions such as in Argentina and Brazil ($95%) [71,[73][74][75][76]. These low coverage rates are due to multiple reasons such as concerns about vaccine safety, low perceived risk of influenza infection and lack of awareness and of recommendations by healthcare professionals [77,78].…”
Section: Influenzamentioning
confidence: 99%